Assessment of Relationship between Various Jumps and Throwing Performance in Judo: - (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This study was conducted to assess the relationship between various jumps and throwingperformance in Judo. This study was conducted on 10 all India Inter-varsity level male subjects. Theyhad participated in intervarsity or higher level of competitions. Subjects performance was recorded onRCMJ (Repeated counter movement jump), CMJ (Counter movement jump), CMJAT (counter movementjump with arm thrust). All these jumps were recorded using G-Sensor device. The device was fixed at thelevel of L5 (5th Lumbar disk). Subjects throwing performance was taken as dependent variables for thestudy. They were asked to perform maximum number of throws of IpponSeoiNage technique in oneminute. Pearson‘s r was calculated as to provide statistical validity to findings of this study. Level ofsignificance was set at 0.05. Out of three selected jumps two (Counter movement jump with arm thrust,Repeated counter movement jump) were found to be significantly correlated with throwing performancein Judo.